Correct use of linking verbs in statements to students in 10th basic education atahualpa high school 2016 2017 academic year - Ontaneda Collaguazo, Gladys Irene (Machala : Universidad Técnica de Machala, 2016)
The main objective of this project is to demonstrate the methodologies in teaching the correct use of linking verbs. speaking in methodologies we should use the following interrogations: what to teach? how to teach and why teach it? these type of interrogates are necessary to elaborate them within the process of teaching, especially in all aspects. in another note the teaching has to be clear and understanding during the time that the lesson is occurring. using methods that can go with the group of students who are being taught at that time, at the same time construct a significant and meaningful teaching to the students. for the north american theorist david ausubel, the teaching that is significant is the one that allows the students to relate the new information with the one they owe, restoring and reconstructing both information in the process. learning implies the possibility of significantly ascribe meaning to what is learned from what is already known. this process results in performing effectively integrated in cognitive learning structure the learner, so that the comprehensive memorization and ensures functionality. it therefore seems justified and desirable that in school teaching and learning situations pursue the realization of such significant learning as possible, since their profitability is remarkable. what needs to be found in the development of this project is to know what methods can be used to teach, the correct use of the linking verbs in different sentences. for this project we will use the investigation as a primary tool.
Keywords: KEYWORD; METHOD; TEACHING; EDUCATING; LINKING VERB